Asymmetric synthesis of ent-anorisol A and its stereoisomers and confirmation of the absolute configuration of anorisol A isolated from Anogeissus rivularis - Chatpreecha R. (2023)
Asymmetric synthesis of (2 S,3 S,4 R,5 S)-2-(2,4-dihydroxyphenyl)-5-(4-methoxyphenyl)-3,4-dimethyltetrahydrofuran named as ent-anorisol A was accomplished. The uncommon relative 2,3-anti-3,4-syn-4,5-syn stereochemistry across tetrahydrofuran (THF) ring of ent-anorisol A was constructed with high yield and good stereoselectivity via an acid-catalyzed direct cyclization of unprotected chiral 1,4-diarylbutane-1,4-diol with non-symmetrical aromatic rings. Except for the sign of the specific rotation value, the spectroscopic data of the synthetic ent-anorisol A are in good agreement with those reported for natural anorisol A isolated from Anogeissus rivularis. In addition, (2 R,3 S,4 R,5 R) and (2 S,3 S,4 R,5 R) isomers of anorisol A were also synthesized. Comparison of the specific rotation value and the experimental electronic circular dichroism (ECD) data of natural anorisol A with those of the synthesized ent-anorisol A, (2 R,3 S,4 R,5 R), and (2 S,3 S,4 R,5 R) derivatives confirms the 2 R,3 R,4 S,5 R configurations assigned for natural anorisol A.